Pemberdayaan Ibu-Ibu Majlis Al Muttaqien dalam Budidaya Tanaman Dandang Gendis sebagai Larutan Kumur untuk Kesehatan Rongga Mulut - Yenny Pragustine; Tri Erri Astoeti; Rahmi Amtha; Moehamad Orliando Roeslan (JURNAL ABDIMAS KESEHATAN TERPADU, 2022)
Dandang gendis is a herbal plant that is widely found in Asia. The plant has many benefits, in some South Asia country they used as antidote for snake venom or bug bites. In dentistry, the plant has been developed to help the healing process of the mucosa in the oral cavity. The background of this Community Service (PkM) activity is the lack of knowledge of housewives regarding the importance of maintaining their family’s oral health and herbal plants that can be used to maintain the health of the oral cavity. The purposes of this activity were to give information about oral health maintenance and introduce the utilization of dandang gendis leaves as a mouthwash solution for the family’s oral health, especially in the Ancol area. This PkM activity is expected to help housewives in maintaining the health of their family's oral cavity by using dandang gendis plants. The implementation was carried out offline on 26th March 2022 by giving lectures regarding the maintenance of oral health, introduction to dandang gendis and the use of dandang gendis leaves as a mouthwash solution, then the activity continued with discussion. The results showed that there is knowledge improvement based on the differences results of pre and post tests carried out.